(untitled) (Revista de História da UEG (REVHIST), 2020)
This study aims to reflect the process of catholicization of the region of the ancient far north of Goiás, through education, a process triggered by the Orionite Catholic missionaries in the 1950s and 1960s. The course of the research that gave rise to this study consisted in the analysis of sources that are the pieces of memory of the own missionaries. The methodology consisted in the reading of these works from studies in the field of cultural history. The critical analysis employed in the research meant observing these works so that we could also extract what they sometimes intended to omit, that is, the outspokenness of the speeches, unveiling the interests, objectives and projects that these missionaries had for the region. The justification for this study is the need to historicize these works, which certainly contributes to the understanding of part of the region’s history, through the hypothesis that education and religion may have been associated as an instrument of catholicization of the ancient far north of Goiás, in the approach. Keywords: Orionite. Goiás. Education. Catholicization.